Improvement of seed quality and field emergence of Fusarium moniliforme infested sorghum seeds using biological agents - Raju, N.S.; Niranjana, S.R.; Janardhana, G.R.; Prakash, H.S.; Shekar Shetty, H.; Mathur, S.B. (Copenhagen (Dinamarca), 1999)
Sumario (En)
24 ref.
Keywords: SORGHUM BICOLOR; GIBBERELLA FUJIKURI; ENFERMEDADES DE LAS PLANTAS; CONTAMINANTES; CALIDAD; SEMILLAS; FUSARIUM